PEMBERDAYAAN MASYARAKAT BIDANG EKONOMI MELALUI UMKM GIPANG SINGKONG TIGA DARA DI KELURAHAN BULAKAN CIBEBER KOTA CILEGON - Fatari Fatari; Freza Yolandani; Bela Silpia; Ernawati Ernawati; Ade Putra Irawan; Nyssa Salwa (Indonesian Collaboration Journal of Community Services, 2023)
Efforts to empower the community's economy are deliberate and planned actions with the aim of changing the economic conditions of the community, both on an individual and group scale, in order to overcome problems related to improving the quality of life, self-sufficiency and welfare. The target of this activity, especially in the Bulakan urban village, is to improve the economy of the people in the area. This activity aims to provide a deeper understanding to the people of the Buakan sub-district regarding the management of micro, small and medium enterprises (MSMEs), so that they can encourage rapid community economic growth, as well as ensure the sustainability of MSMEs in the future and increase family income. The approach used in this Community Service (PkM) activity is to provide assistance to the owner of the Gipang Cassava 3 Dara UMKM business, namely Mrs. Santi, who is located in the Bentola RT environment. 05/01 Bukan Cibeber sub-district, Cilegon city. It was carried out by KKM Group 75 students and field supervisors and lecturers. After the socialization activities, MSME actors expressed satisfaction and understood and understood what had been conveyed. The hope is that after understanding digital marketing, you can increase sales results